2022
DOI: 10.3390/medicina58121816
|View full text |Cite
|
Sign up to set email alerts
|

D-Ribose-Induced Glycation and Its Attenuation by the Aqueous Extract of Nigella sativa Seeds

Abstract: Background and Objectives: Glycation and oxidative stress are the major contributing factors responsible for diabetes and its secondary complications. Aminoguanidine, a hydrazine derivative, is the only approved drug that reduces glycation with its known side effects. As a result, research into medicinal plants with antioxidant and antiglycation properties is beneficial in treating diabetes and its consequences. This investigation aimed to examine the efficacy of the aqueous extract of Nigella sativa seeds aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Aminoguanidine (AG) is a hydrazine derivative and has been used as a representative compound for glycation inhibition and has served as a positive control in numerous experimental setups [20,21,[45][46][47]. AG hydrochloride (Sigma-Aldrich, St. Louis, MO, USA) was used as a positive deglycation agent.…”
Section: Aminoguanidinementioning
confidence: 99%
See 1 more Smart Citation
“…Aminoguanidine (AG) is a hydrazine derivative and has been used as a representative compound for glycation inhibition and has served as a positive control in numerous experimental setups [20,21,[45][46][47]. AG hydrochloride (Sigma-Aldrich, St. Louis, MO, USA) was used as a positive deglycation agent.…”
Section: Aminoguanidinementioning
confidence: 99%
“…AG hydrochloride (Sigma-Aldrich, St. Louis, MO, USA) was used as a positive deglycation agent. Given the known side effects shown in previous studies, AG is not used for clinical purposes [45,47].…”
Section: Aminoguanidinementioning
confidence: 99%
“…Simultaneously, parallel samples containing the respective extracts underwent an identical incubation protocol to rigorously evaluate and compare their efficacy in preventing glycation. Aminoguanidine (AG), a well‐established positive control, was consistently applied at a concentration of 1 mM [29,30] …”
Section: Methodsmentioning
confidence: 99%
“…This result aligns closely with the findings of Lai et al ( 2019), who reported a doubling time of 11.75 days for a similar culture. [29]…”
Section: Growth Curve Of S Platensismentioning
confidence: 99%
“…A spectrum of both qualitative and quantitative methodologies has been developed, illuminating the intricacies of this phenomenon [7]. Traditional glycated materials undergo meticulous examination via diverse techniques, including spectrophotometric and electrophoretic methods [8]. Recent strides have introduced sophisticated tools like spectrofluorimetry, high-performance liquid chromatography (HPLC), and liquid chromatography-mass spectrometry (LC-MS), offering heightened precision in quantifying AGEs and evaluating glycation-related processes [9].…”
Section: Introductionmentioning
confidence: 99%